2020
DOI: 10.1139/cjes-2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Research on the fracture structure and activity of the Qinling Mountains thrust nappe system in western Hubei

Abstract: The Western Hubei section of the Liangyun fault is an important structural belt of the southern Qinling Mountains thrust nappe system. As the significant activity of the Liangyun fault since the Quaternary has led to high seismic risk in the surrounding area, the research on the characteristics and activity of fault structure is of great significance for deepening the construction of a seismic safety system in this area. In this study, we conducted a field geology survey combined with quartz optical stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In recent years, with seismic exploration, a series of achievements have been made in the survey of site engineering, geological conditions, and buried faults. Lin Song et al [8][9][10] identified the geometric features of the Danjiang Fault, Liangyun Fault, and Baihe-Gucheng Fault through seismic reflection and analyzed the stress structure of the region. Liu Baojin et al [11] exposed explicitly the developmental characteristics of the Pengzhou buried fault in the frontal area of Longmen Shan through the high-resolution seismic reflection profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with seismic exploration, a series of achievements have been made in the survey of site engineering, geological conditions, and buried faults. Lin Song et al [8][9][10] identified the geometric features of the Danjiang Fault, Liangyun Fault, and Baihe-Gucheng Fault through seismic reflection and analyzed the stress structure of the region. Liu Baojin et al [11] exposed explicitly the developmental characteristics of the Pengzhou buried fault in the frontal area of Longmen Shan through the high-resolution seismic reflection profiles.…”
Section: Introductionmentioning
confidence: 99%